PENERAPAN MODEL PENANGGULANGAN PENYALAHGUNAAN NARKOBA - Achmadi Jayaputra (Sosio Informa, 2003)
The Implementation of Drug Abuse Combating Model.Drug abuse that has influenced urban as ewwl as rural societies, could be seen from abuses, uses and the way they are. In jakarta, and in Tanah Abang district in particular, local community has developed a community-based social services for the drug addict. This modelseemstobe effective to prevent drug abuse problem. However as an element on social capital,networks that link members of the community was a new self-induced nitiative the model it self still need of socialization.Kata Kunci: Penyalahgunaan narkoba, posyanmas, model penanggulangan